PELAKSANAAN FUNGSI PEMERINTAH DAERAH DALAM PENERTIBAN PERTAMBANGAN DI KABUPATEN TIMOR TENGAH SELATAN PROVINSI NUSA TENGGARA TIMUR - Ampera Seke Selan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Abstract : This article presents the problem of illegal mining carried out by residents, and the extent to which the South Central Timor Regency (TTS) government has issued mining permits. The main issue is whether the regional government has the authority to regulate mining control and supervision activities in the manganese rock area of TTS Regency, East Nusa Tenggara (NTT) Province? And what are the efforts of the local government towards the factors that hinder it. The method used in this research is empirical legal research. It was found that according to regional regulations, the regional government was given authority both from the regions themselves and from the central government, but this has not been maximally implemented in TTS District. It was also found that the local government had not controlled illegal miners' permits, and seemed to allow stone miners to get up illegally which was very troubling to the community. It is hoped that the regional government of TTS Regency, through the relevant technical services, will address environmental problems and resonate areas where there is potential for manganese. There needs to be a price fixing that is directly claimed by the regional government for the effectiveness of regional income including community income from the natural potential of manganese in the TTS Regency area. Keywords: Regional Government Authorities, Ordering Permits, Mining. Abstrak : Tulisan ini menampilkan problem penambangan liar yang dilakukan oleh warga, dan sejauh mana pemerintah daerah Kabupaten Timor Tengah Selatan (TTS) menerbitkan izin pertambangan. Masalah pokoknya adalah apakah Pemerintah daerah berwenang dalam penertiban kegiatan Pengendalian dan pengawasan pertambangan di kawasan batu mangan Kabupaten TTS, Provinsi Nusa Tenggara Timur (NTT)? Dan apa upaya Pemda terhadap faktor yang menghambatnya. Metode yang digunakan penelitian ini yakni penelitian hukum secara emperis. Diitemukan bahwa secara regulasi pemda diberi kewenangan baik dari daerah sendiri maupun dari pemerintah pusat akan tetapi belum diterapkan secara maksimal di Kabupaten TTS. Ditemukan juga bahwa pemda belum mengendalikan izin penambang liar, dan terkesan membiarkan penambang batu bangun liar yang sangat meresahkan masyarakat. Diharapkan pemda Kabupaten TTS melalui dinas teknis terkait mengatasi masalah lingkungan dan adanya resonasi wilayah yang terdapat potensi batu mangan. Perlu adanya penetapan harga yang langsung diklaim oleh pemda guna efektifnya pendapatan daerah termasuk pendapatan masyarakat dari potensi alam batu mangan di wilayah Kabupaten TTS. Keywords : Kewenangan Pemda, Penertiban Izin, Tambang.